134k views
5 votes
Helpppp ASAP
Drag Values To complete each equation

Helpppp ASAP Drag Values To complete each equation-example-1

2 Answers

2 votes

Answer:

hi 1 and 17^9

Explanation:

Helpppp ASAP Drag Values To complete each equation-example-1
User Rdougan
by
5.0k points
5 votes

Given:

Part A:
(\left(17^(3)\right)^(6) \cdot 17^(-10))/(17^(8))

Part B:
\left(17^(6)\right)^(3) \cdot 17^(-9)

To find:

The value of each expression.

Solution:

Part A:

Using exponent rule:
(a^m)^n=a^(mn)


$(\left(17^(3)\right)^(6) \cdot 17^(-10))/(17^(8))=(\left(17\right)^(3* 6) \cdot 17^(-10))/(17^(8))


$=((17)^(18) \cdot 17^(-10))/(17^(8))

Using exponent rule:
a^m \cdot a^(n)= a^(m+n)


$=((17)^(18+(-10)))/(17^(8))


$=(17^(8))/(17^(8))

Cancel the common factor, we get

= 1


$(\left(17^(3)\right)^(6) \cdot 17^(-10))/(17^(8))=1

Part B:


\left(17^(6)\right)^(3) \cdot 17^(-9)

Using exponent rule:
(a^m)^n=a^(mn)


\left(17^(6)\right)^(3) \cdot 17^(-9)=\left(17\right)^(6* 3) \cdot 17^(-9)


=(17)^(18) \cdot 17^(-9)

Using exponent rule:
a^m \cdot a^(n)= a^(m+n)


=(17)^(18+(-9))


=17^9


\left(17^(6)\right)^(3) \cdot 17^(-9)=17^9

User CharlyAnderson
by
4.9k points